(untitled) (International Journal of Food and Nutritional Sciences, 2022)
We analyse the effect of chemical reaction and radiation absorption on unsteady convective Heat and Mass Transfer flow of viscous fluid through a Porous Medium in a vertical channel in the presence of Heat generating sources. The unsteadiness in the flow is due to a traveling thermal wave imposed on the boundary y=+L. Taking the aspect ratio δ